Potentials of 24-hour esophageal рН monitoring in diagnostics and treatment efficacy control of gastroesophageal reflux disease - N. L. Dzhakhaya; A. S. Trukhmanov; M. Yu. Kon’kov; O. A. Sklyanskaya; A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate potentials of 24-hour esophageal рН monitoring for antisecretory treatment adjustment in patients with gastroesophageal reflux disease (GERD).Material and methods. Overall 58 patients with GERD were included in original study (main group) and 18 healthy volunteers formed a control group.Results. At evaluation of all pH-metry parameters, it has been noticed, that mostly two parameters – the fourth (total time of esophageal рН is under 4) and the seventh (cumulative, or DeMeester score) – show stable steady stage-wise increase of scores related to increase in severity of esophageal mucosa damage. At analysis of the first рН-gramm parameter (total reflux number) it was found, that average number of episodes was highest at erosive esophagitis of I stage. At the II stage this number decreases, but remains higher, than at non-erosive esophagitis, and at III and IV stages drops to the level of the latter. Statistically significant differences between main and control groups were revealed for all scores. Differences between pH-metry parameters of control group and normal scores were not statistically significant.Conclusions. Introduction of 24-hour pH-metry of the esophagus in clinical practice enables monitoring of gastroesophageal refluxes, detection of their type (acidic, alkalinic), number (less or higher than 49 episodes per day), estimation of treatment efficacy. When necessary it helps to carry out treatment adjustment and to choose the most acceptable mode of treatment.